2012
DOI: 10.4103/1947-2714.94944
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of TNF-α and IL-6 levels in obese and non-obese diabetics: Pre- and postinsulin effects

Abstract: Background:Type 2 diabetes (T2DM) mellitus is a serious implication of obesity. The effect of insulin therapy on levels of inflammatory markers among obese and non-obese diabetics has been inadequately studied.Aim:The study aimed to analyze the preinsulin and postinsulin levels of tumor necrosis factor α (TNF-α) and IL-6 in nonobese and obese T2DM patients.Materials and Methods:We assessed TNF-α and IL-6 levels in healthy controls (n=10) and diabetic patients (obese and nonobese; n=20 each) and analyzed the po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
55
3
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(63 citation statements)
references
References 15 publications
4
55
3
1
Order By: Relevance
“…Significantly higher levels of TNF-α in the blood of patients with morbid obesity recorded in the current study are consistent with the results reported by Solá et al (2009) patients with morbid obesity and by Goyal et al (2012) in patients with severe obesity (BMI>30 kg/m 2 ) and type 2 diabetes. Cardillo et al (2006) studied 26 low-fat and 27 low-carbohydrate participants with a BMI of >35 kg/m 2 and found no differences in the concentration of TNF-α after 6 and 36 months of the observation period, independent of the diet regimen.…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Significantly higher levels of TNF-α in the blood of patients with morbid obesity recorded in the current study are consistent with the results reported by Solá et al (2009) patients with morbid obesity and by Goyal et al (2012) in patients with severe obesity (BMI>30 kg/m 2 ) and type 2 diabetes. Cardillo et al (2006) studied 26 low-fat and 27 low-carbohydrate participants with a BMI of >35 kg/m 2 and found no differences in the concentration of TNF-α after 6 and 36 months of the observation period, independent of the diet regimen.…”
Section: Discussionsupporting
confidence: 82%
“…Increased levels of IL-6 were found in the blood of patients with morbid obesity (Solá et al, 2009), in patients with type 2 diabetes accompanied by obesity (Goyal et al, 2012), and in patients with type 2 diabetes with accompanying albuminuria (Czyżewska et al, 2012). An effect of weight loss on serum IL-6 in obese patients undergoing weight reduction was observed by OlszaneckaGlinianowicz et al (2011).…”
Section: Inmentioning
confidence: 99%
“…Metformin is frequently given to T2DM in combination with insulin [23]. Previous studies have shown that intensive insulin therapy reverses the decrease in adipocyte glucose transport activity in T2DM [24] and counters inflammation by decreasing levels of IL-6 and TNFα [25]. Insulin is commonly used in in vitro studies to induce adipogenesis, as it triggers a series of transcription factors that drive differentiation of pre-adipocytes into mature adipocytes including phosphorylation and activation of CREB [26] and PI 3-kinase [27].…”
Section: Introductionmentioning
confidence: 99%
“…The trends in the prevalence of obesity documented over the last few decades in our country have been alarming, with morbid obesity affecting 5% of Indian population. [3] Insulin resistance is associated with visceral and subcutaneous fat content. [4]…”
Section: Introductionmentioning
confidence: 99%